Hubungan Customer Relantionship Management (CRM) dengan Loyalitas Pasien di Bagian Administrasi Rumah Sakit Umum Daerah Pademangan - Zahra Aurelia; Ria Efkelin; Sarah Geltri Harahap (Malahayati Nursing Journal, 2024)
ABSTRACT Patient loyalty is greatly influenced by the perception of the patient's family and society. In addition to technical care, it is also important to pay attention to comfort and daily interactions with patients. This shows the company's efforts in getting to know, attracting and retaining patients. Customer Relationship Management (CRM) helps analyze visit patterns, service preferences and patient needs, so that administrative staff can provide more personalized and relevant services. This research uses quantitative methods with a cross-sectional design and involves patients who have received administrative services at least twice at the Pademangan Regional General Hospital. The sample was selected using Purposive Sampling with a total of 100 respondents. The research results showed that 108.1% of respondents were satisfied with competence and good service, and 109.1% were satisfied with good technology. Overall, there is a positive relationship between competence, service, knowledge and technology and patient loyalty. Most respondents (97.8%) rated CRM as good on the competency, service, knowledge and technology indicators.  Keywords: Patient Loyalty, Customer Relationship Management, Administrative ServiceABSTRAK Loyalitas pasien sangat dipengaruhi oleh persepsi keluarga pasien dan masyarakat. Selain perawatan teknis, penting juga memperhatikan kenyamanan dan interaksi harian dengan pasien. Ini menunjukkan upaya perusahaan dalam mengenal, menarik, dan mempertahankan pasien. Customer Relationship Management (CRM) membantu menganalisis pola kunjungan, preferensi layanan, dan kebutuhan pasien, sehingga staf administrasi bisa memberikan layanan yang lebih personal dan relevan. Penelitian ini menggunakan metode kuantitatif dengan desain cross-sectional dan melibatkan pasien yang telah menerima layanan administrasi minimal dua kali di Rumah Sakit Umum Daerah Pademangan. Sampel dipilih menggunakan Purposive Sampling dengan total 100 responden. Hasil penelitian menunjukkan bahwa 108,1% responden puas dengan kompetensi dan pelayanan yang baik, serta 109,1% puas dengan teknologi yang baik. Secara keseluruhan, terdapat hubungan positif antara kompetensi, pelayanan, pengetahuan, dan teknologi dengan loyalitas pasien. Sebagian besar responden (97,8%) menilai CRM pada indikator kompetensi, pelayanan, pengetahuan, dan teknologi sebagai baik.Kata kunci: Loyalitas Pasien, Customer Relationship Management, Pelayanan Administrasi